Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1242/jeb.198028
|View full text |Cite
|
Sign up to set email alerts
|

PPAR expression, muscle size, and metabolic rates across the Gray catbird's annual cycle are greatest in preparation for fall migration

Abstract: Phenotypic flexibility across the annual cycle allows birds to adjust to fluctuating ecological demands. Varying energetic demands associated with time of year have been demonstrated to drive metabolic and muscle plasticity in birds, but it remains unclear what molecular mechanisms control this flexibility. We sampled gray catbirds at five stages across their annual cycle: tropical overwintering (January), northward spring (late) migration (early May), breeding (mid June), the fall pre-migratory period (early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
(93 reference statements)
0
17
2
1
Order By: Relevance
“…In contrast to our findings, the few studies to examine oxidative challenges in wild migratory passerines have found increased oxidative damage associated with flight (Jenni-Eiermann et al, 2014;Skrip et al, 2015). However, migratory birds undergo seasonal, photoperiod-induced, physiological changes to enhance fat catabolism and, ultimately, their metabolic output (DeMoranville et al, 2019;Dick, 2017;Guglielmo et al, 2002;Jenni and Jenni-Eiermann, 1998;Price et al, 2011) that may result in an especially high oxidative challenge not experienced by our non-migratory zebra finches. Additionally, how quickly a bird shifts to using fat as fuel may inherently affect the risk of lipid peroxidation associated with flight.…”
Section: Hypothesis 3inevitable Damagecontrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast to our findings, the few studies to examine oxidative challenges in wild migratory passerines have found increased oxidative damage associated with flight (Jenni-Eiermann et al, 2014;Skrip et al, 2015). However, migratory birds undergo seasonal, photoperiod-induced, physiological changes to enhance fat catabolism and, ultimately, their metabolic output (DeMoranville et al, 2019;Dick, 2017;Guglielmo et al, 2002;Jenni and Jenni-Eiermann, 1998;Price et al, 2011) that may result in an especially high oxidative challenge not experienced by our non-migratory zebra finches. Additionally, how quickly a bird shifts to using fat as fuel may inherently affect the risk of lipid peroxidation associated with flight.…”
Section: Hypothesis 3inevitable Damagecontrasting
confidence: 93%
“…Flapping flight often increases metabolic rate up to 30 times basal metabolic rate (Nudds and Bryant, 2000;Tatner and Bryant, 1986;Wikelski et al, 2003), with associated increases in acute RS production (Costantini, 2014;Costantini et al, 2010;Jenni-Eiermann et al, 2014). In addition, passerines primarily use fat as fuel during flights (Bairlein, 1990;Hambly et al, 2002;Jenni and Jenni-Eiermann, 1998), particularly during migration, when the capacity for fat metabolism is highest (DeMoranville et al, 2019;Gerson and Guglielmo, 2013;Jenni-Eiermann et al, 2002;McWilliams et al, 2004;Price et al, 2011). Relying on fat as fuel may also increase RS production as fats are catabolized (Costantini et al, 2007;Skrip et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic costs of flying are long established (Bishop and Butler, 2015) as are the many physiological adjustments that enable the long-duration flights achieved by birds during migration, including increased oxidative enzymes (McClelland, 2004;Weber, 2011;Banerjee and Chaturvedi, 2016;Dick and Guglielmo, 2019;Carter et al, 2021) and fatty acid transport and oxidation (Guglielmo et al, 2002;McWilliams et al, 2004McWilliams et al, , 2021Guglielmo, 2018), as well as hypertrophy of key organs such as pectoralis and liver (Marsh, 1984;Dietz et al, 1999;Piersma et al, 1999;Lindström et al, 2000;DeMoranville et al, 2019). These biochemical adjustments are associated with upregulation of genes responsible for regulating metabolism (PPARγ and PPARα), and key genes responsible for fat transport (FABPpm, CD36, and H-FABP) and fat oxidation (ATGL, LPL, and MCAD) among others (McFarlan et al, 2009;Zhang et al, 2015;Corder et al, 2016;DeMoranville et al, 2019). Furthermore, experimental studies demonstrate that longdistance flight training in a wind-tunnel upregulates genes involved in mitochondrial metabolism and fat utilization in pectoralis but not liver (DeMoranville et al, 2020).…”
Section: Is Oxidative Damage An Inevitable Consequence Of Oxidative Challenges During a Flight?mentioning
confidence: 99%
“…fatty acid translocase/CD36 or plasma membrane-bound fatty acid binding protein) and fatty acid oxidation (e.g. activation of PPARs, enzymes such as β-hydroxyacyl-Coenzyme-A dehydrogenase or carnitine palmitoyl transferase) are upregulated prior to seasonal migration [85][86][87]. Further, migratory flights are fueled by high levels of circulating triglycerides transported by very low density lipoproteins (VLDLs) [21].…”
Section: Plos Onementioning
confidence: 99%